Etanol e suas associações : efeitos comportamentais e cardiovasculares - Engi, Sheila Antonagi (Universidade Federal de São Carlos, 2016)
Alcohol abuse is a worldwide problem with concomitant medical, social and economic costs. In Brazil, epidemiological data show an increase in the abuse of illicit and licit drugs, such as ethanol and steroids. Studies indicate that physical exercise influences ethanol consumption and preference and is positively correlated with steroids abuse. Despite many evidences, there is no study about the association between ethanol consumption, physical exercise and steroids abuse. In the present study, we investigated 1) the effects of physical exercise associated to testosterone treatment in ethanol intermittent access drinking; 2) consequences of the association between physical exercise, ethanol intermittent access and chronic testosterone treatment upon the cardiovascular system of rats. Many studies suggest that the mTORC1- mammalian target of rapamycin complex participates in the mechanisms related to ethanol abuse. In this way, we investigated the mTORC1 role in the ethanol intermittent access consumption maintenance. Our results showed that a) physical exercise improved treadmill performance in rats and did not change ethanol consumption; b) ethanol voluntary consumption was not affected either by physical exercise or by testosterone treatment; c) ethanol voluntary intermittent access did not change basal arterial pressure and heart rate; d) testosterone treatment caused rest bradycardia; e) ethanol consumption and testosterone treatment altered vascular reactivity to vasoactive agents, that was also altered by physical exercise. These results show the first evidence of ethanol intermittent access and testosterone treatment on cardiovascular functions in trained rats. Our results also suggest that the downstream mTORC1 pathway is related to excessive and abusive ethanol consumption.
Keywords: Dependência; Etanol; Toxicidade cardiovascular; mTORC1; CIENCIAS BIOLOGICAS::FISIOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA CARDIOVASCULAR; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS